The Effect of Financial Literacy, Financial Risk Tolerance, and Financial Socialization Agents on Stock Investment Decision in The Millennial Generation - Hendarto, Kevin; Anastasia, Njo; Basana, Sautma Ronni (Petra International Journal of Business Studies, 2021)
This study aim to determine financial literacy, financial risk tolerance, and financial socialization agents effect/influence on stock investment decisions in the millennial generation. The research was conducted by distributing questionnaires to 400 millennial generation stock investors in Indonesia. The data analysis method by Structural Equation Modeling (SEM) using the SmartPLS 3.2.7 program. The results show that financial literacy has a significant effect on investment decisions. Financial risk tolerance has significant effect on investment decisions, meanwhile financial socialization agents do not have a significant effect on investment decisions.